Food as a new old commons: A paradigm shift for human flourishing - Vivero-Pol, Jose Luis (World Nutrition, 2019)
The industrial food system, which is becoming highly dominant, is increasingly failing to fulfil its basic functions: producing food in a sustainable manner, feeding people adequately and avoiding hunger. As hunger remains steadily high and obesity numbers do not cease to grow in a world that is overconsuming natural resources far beyond planetary boundaries, producing food unsustainably and wasting one third of it, there is a need to bring unconventional perspectives into the debate on possible solutions for a transition towards a fairer and sustainable food system. The dominant paradigms that have sustained human development and economic growth during the twentieth century (productivism, consumerism, individualism, survival of the fittest, the tragedy of the commons and endless growth) do not provide viable solutions to the multiple crises and the current challenges. Considering food as a commons can be an alternative paradigm worth exploring. The food commons, anchored to the adequate valuation of the multiple dimensions of food to humans, can provide a discourse of convergence that embraces contemporary (i.e. urban innovations) and customary (i.e. indigenous practices) food activities, being at the same time the aspirational vision that coalesce the different collective actions for food into a networked web that relentlessly grows to challenge and render obsolete the industrial food system that only values the economic dimension of food as a commodity, keeps food producers hungry and makes food consumers obese.